Inflation Persistence in Brazil : A Cross Country Comparison - Roache, Shaun (IMF Working Papers; Working Paper ;, 2014)
Inflation persistence is sometimes defined as the tendency for price shocks to push the inflation rate away from its steady state-including an inflation target-for a prolonged period. Persistence is important because it affects the output costs of lowering inflation back to the target, often described as the 'sacrifice ratio'. In this paper I use inflation expectations to provide a comparison of inflation persistence in Brazil with a sample of inflation targeting (IT) countries. This approach suggests that inflation persistence increased in Brazil through early 2013, in contrast to many of its IT peers, mainly due to 'upward' persistence. The 2013 rate hiking cycle may have contributed to some recent decline in persistence.